2016
DOI: 10.1089/jwh.2015.5529
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Inflammation with Premenstrual Symptoms

Abstract: Background: About 80% of women experience premenstrual symptoms (PMSx), and about 50% of women seek medical care for them, posing a large medical care burden. However, despite women's use of antiinflammatory agents for relief from these symptoms, and the fact that anti-inflammatory agents provide relief from some PMSx, the relationship of inflammation to PMSx has not been well investigated. Methods: We, therefore, undertook the present cross-sectional analyses using baseline data from the longitudinal Study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 26 publications
3
55
0
1
Order By: Relevance
“…Furthermore, repeated hs-CRP serum concentrations correlated significantly and positively with the symptom scores. A similar association was found in the study by Gold et al [19]. These authors found that older reproductive age women with serum level of hs-CRP higher than 3 mg/L had about 30% higher probability of premenstrual mood symptoms and 40% higher probability of abdominal cramps and back pain when compared to women with lower level of hs-CRP.…”
Section: Premenstrual Syndrome and Inflammationsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, repeated hs-CRP serum concentrations correlated significantly and positively with the symptom scores. A similar association was found in the study by Gold et al [19]. These authors found that older reproductive age women with serum level of hs-CRP higher than 3 mg/L had about 30% higher probability of premenstrual mood symptoms and 40% higher probability of abdominal cramps and back pain when compared to women with lower level of hs-CRP.…”
Section: Premenstrual Syndrome and Inflammationsupporting
confidence: 86%
“…Furthermore, progesterone, due to its ant-inflammatory action, enables embryo implantation in female uterus during the pregnancy [25]. The increase of inflammatory hs-CRP and interleukins should be thus expected during the premenstrual period when progesterone level decreases, as observed in studies described above [19][20][21]. It is also possible that the low level of progesterone during the luteal phase might promote infection and inflammation which results in an increased level of inflammatory proteins such as hs-CRP and interleukins.…”
Section: Progesterone Inflammation and Premenstrual Syndromementioning
confidence: 92%
See 1 more Smart Citation
“…Low‐grade inflammation has been reported to be associated with an astounding number of conditions and lifestyles felt to be associated with poor health; these conditions represent or reflect minor metabolic stresses. The lengthy (partially cited here) list includes exposure to environmental irritants such as cigarettes, secondhand smoke, sleep deprivation, low levels of physical activity, atrial fibrillation, hypertension, low birth weight, lumbar disc herniation, impaired cognition, low grip strength, polycystic ovary syndrome, living at high altitude (12, 13), prehypertension (14), obstructive sleep apnea (15), premenstrual symptoms (16), a large variety of unhealthy diets (17), hypoxia (18), social isolation (19, 20), being unmarried (21), and aging (22, 23).…”
Section: Low‐grade Inflammationmentioning
confidence: 99%
“…24 CRP levels are positively associated with mood, behavior, pain and physical symptom severity during the menstrual cycle. 25,26 IL-2, IL-4, IL-10, IL-12, and interferon-gamma (IFN-) are also associated with emotional and physical symptom in women with PMS 27 whereby levels of IL-12 and IFN- are more than twice as high in PMS as compared with controls. Nevertheless, there are no studies whether changes in chemokine levels are associated with menstrual cycle symptoms.…”
Section: Introductionmentioning
confidence: 99%